Legal Framework of Indonesia’s Energy Transition: Regional Autonomy and Chinese Investment in Green Development - Adi, Emmanuel Ariananto Waluyo; Ong, William; Siombo, Marhaeni Ria (Pandecta Research Law Journal, 2025)
In response to global efforts to reduce greenhouse gas emissions, Indonesia is promoting the adoption of electric vehicles (EVs), particularly battery-based electric motor vehicles (KBLBB), most of which are imported from China. This initiative aligns with the national commitment to achieve Net Zero Emissions by 2060 and transition from fossil fuels to renewable energy. The government has issued several legal instruments, including Presidential Decree No. 79 of 2023 and Presidential Instruction No. 7 of 2022, the latter mandating the use of KBLBB for official vehicles by regional governments. However, implementation at the regional level remains limited. Despite their potential as role models, local governments have not widely adopted KBLBB, in contrast to the central government. This discrepancy is attributed to the non-binding nature of presidential instructions and the autonomy granted to regional governments under Indonesia's decentralization framework. Using a normative juridical method with statutory and conceptual approaches, this study analyzes the effectiveness and legal enforceability of these policies. The key issue lies in the normative authority of presidential regulations versus local autonomy. The study argues that achieving a just and inclusive energy transition requires equitable adoption of KBLBB across all regions. Where regional governments face financial or infrastructural constraints, central government support is essential. Encouraging foreign particularly Chinese investment could accelerate infrastructure development and expand access to EV technology nationwide. Strengthening legal mandates and enhancing intergovernmental coordination are critical to advancing Indonesia’s sustainable transportation agenda